Integrated Project Delivery: diretrizes para empresas de projeto que atuam em habitação de interesse social - Lins, Deborah Martins de Oliveira (2013)
The “Minha Casa Minha Vida” (MCMV), which aims to reduce the housing deficit, launched its second phase, with a bold goal to hire two million housing units by the year 2014. While this economic environment encouraged companies in the Construction Industry, they were not adequately prepared to absorb the new demands. To reach them, we need to implement innovations in traditional processes of design and construction of this type of housing, increasing productivity, but without loss of quality of the products generated. The projects related to housing construction have become increasingly complex, and has increased the number of projects needed to better execution of the work, causing serious problems of compatibility and rework. In view of the peculiar characteristics of the enterprises of Social Housing (HIS), the profit margins offered by these are greatly reduced, forcing companies to pursue lower production costs and execution time of compression, in order to minimize the incidence of fixed costs. It is worth noting that the initial stages of development, such as program and project are those that present the greatest opportunities for intervention and value. In some countries, especially the United States, these problems have been minimized through approaches such as Integrated Project Delivery (IPD) and the use of design tools such as the Building Information Modeling (BIM). In turn, the vast majority of projects in Brazil, especially the HIS, are not designed with this in mind integration. Within this context, the aim of this work is to propose guidelines for increasing the level of integrated management for design firms that operate in MCMV (range 0-3 minimum wages), based on the principles of IPD. This is a qualitative study with an exploratory-descriptive and research strategy used was the multiple case study, divided into four phases: literature review, exploratory stage, stage of conducting case studies and step analyzes and propositions . Therefore, we carried out a survey to contextualize the partial results of the program and analyze the role of each of the major players involved. There was a peculiarity in the state of Ceará: the Sinduscon-Ce provides companies affiliated three types of architectural design, installations and structures (reference projects). We investigated how was the design process of these types and the level of integration between professionals. The main tool for data collection were semi-structured interviews with the designers, with the representative of Box and Sinduscon. Based on these data, we carried out a cross-sectional analysis of business and design, as well as a diagnosis of these assumptions with respect to the IPD. We also propose an adaptation of the principles of IPD directed to designers Finally, the main contribution of this work is to propose guidelines for increasing the level of integrated management between designers working in MCMV, relating them to the principles of IPD .